Dietary Flavonoids as Modulators of Lipid Metabolism in Poultry - Tan, Zhendong; Halter, Bailey; Liu, Dongmin; Gilbert, Elizabeth R.; Cline, Mark A. (Frontiers in Physiology, 2022)
Flavonoids, naturally-occurring compounds with multiple phenolic structures, are the most widely distributed phytochemicals in the plant kingdom, and are mainly found in vegetables, fruits, grains, roots, herbs, and tea and red wine products. Flavonoids have health-promoting effects and are indispensable compounds in nutritional and pharmaceutical (i.e., nutraceutical) applications. Among the demonstrated bioactive effects of flavonoids are anti-oxidant, anti-inflammatory, and anti-microbial in a range of research models. Through dietary formulation strategies, numerous flavonoids provide the ability to support bird health while improving the nutritional quality of poultry meat and eggs by changing the profile of fatty acids and reducing cholesterol content. A number of such compounds have been shown to inhibit adipogenesis, and promote lipolysis and apoptosis in adipose tissue cells, and thereby have the potential to affect fat accretion in poultry at various ages and stages of production. Antioxidant and anti-inflammatory properties contribute to animal health by preventing free radical damage in tissues and ameliorating inflammation in adipose tissue, which are concerns in broiler breeders and laying hens. In this review, we summarize the progress in understanding the effects of dietary flavonoids on lipid metabolism and fat deposition in poultry, and discuss the associated physiological mechanisms.